PRODUCT QUALITY ABILITY, PRICE AND PRODUCT DESIGN INFLUENCE ADIDAS SHOES PURCHASE DECISION - SUDUNG SIMATUPANG; VIVI CANDRA; DEBI EKA PUTRI; ERNEST GRACE; EKO HAMDANI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
The purpose of this study was to determine the ability of variable product quality, price and product design to purchase decisions made by the football team in Karang Sari Village. The total population of soccer players is 80 people and with the purposive sampling method it was found that there were 35 users of Adidas shoes. By using the validity and reliability test that the data under study the results are valid and reliability. Furthermore, the hypothesis results found that simultaneously product quality, price and product design have a positive and significant effect on purchasing decisions, but for the partial test that prices have a negative and insignificant effect on purchasing decisions, for product quality and product design have a positive and significant effect on purchasing decisions.